An assessment of the effectiveness and scale of tax expenditures to support investments and priority sectors in G20 countries - Svetlana Evgen'evna Demidova; Yuliya Tyurina; Anastasia Kulachinskaya; Olga Buzdalina; I. V. Ilʹin; Victoriya Razletovskaia; Chulpan A. Misbakhova (Economies, 2024)
Tax expenditure management is one of the tools for conducting responsible fiscal policy. Unlike direct expenditures, tax expenditures do not consume resources, but allow the achievement of certain social and economic goals. The purpose of this study is to test the hypothesis of the expediency of using the mechanism of tax expenditures to influence investment activities and the development of priority sectors of the economy. The object of this study was a sample of nine countries of the G-20 group, whose reports provided data on the share of tax expenditures related to investment support and stimulating the development of priority sectors of the economy. The practice of generating reports on tax expenditures is quite common in developed countries, but there are several limitations for cross-country comparison: national characteristics of fiscal elements, and the level of openness and transparency of data on tax expenditures. The scale of using tax expenditures is determined by the multidimensional average method; countries are rated according to the value of the integral indicator. The scale of tax breaks determines the position in the ranking. The effectiveness of using tax breaks is assessed through the coefficient of increase in investment and the coefficient of increase in industrial production. The assessment results show whether economic indicators are outpacing the growth rate of tax benefits and preferences. A study of panel data revealed the average degree of influence of the total amount of tax expenditures on the dynamics of capital investments. The allocation of a target group of tax expenditures related to investment support showed a weak degree of influence on the dynamics of capital investment volumes. The results obtained can be explained by the fact that the allocation of a target group of tax expenditures may not reflect the full range of tax benefits provided to support investments, which is due to the peculiarities of the system of accounting and assessment of tax expenditures in a particular country. In addition, the contribution of tax expenditures may be insignificant if direct forms of support prevail.
Keywords: 330; efficiency of tax expenditures; investments; priority sectors; scale of tax expenditures; targeted tax incentives and preferences; tax benefits; tax expenditures